2020
DOI: 10.1093/rpd/ncaa073
|View full text |Cite
|
Sign up to set email alerts
|

Eye Lens Dose Optimization Through Gantry Tilting in Brain Ct Scan: The Potential Effect of the Radiological Technologists’ Training

Abstract: This study was designed to evaluate the effect of the radiological technologists’ training on optimising the eye lens dose in brain computed tomography (CT) examinations. The lens dose of 50 adult patients was measured using thermoluminescent dosimeters before and after technologists’ training. Dose values of lenses, dose length product (DLP), volumetric CT dose index (CTDIvol) as well as image quality in terms of quantitative (contrast to noise ratio and signal to noise ratio) and subjective (artefact) parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A study carried out in Iran in 2020 by Ebrahiminia et al. ( 16 ) found that the training of the radiological technologists resulted in the reduction of radiation dose to the lens by 83%. In our study, we could not calculate a similar percentage, since the dose estimations for the Class B studies could not be calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in Iran in 2020 by Ebrahiminia et al. ( 16 ) found that the training of the radiological technologists resulted in the reduction of radiation dose to the lens by 83%. In our study, we could not calculate a similar percentage, since the dose estimations for the Class B studies could not be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the radiation dose of lenses can also be reduced by adapting organ-based dose modulation ( 15 ) , or optimising gantry tilt angle. When the gantry tilt angle is aligned with the supraorbitomeatal line (SOML, Figure 1 ), the lens is not exposed to the primary beam and the radiation dose is reduced by 75–93% ( 16–19 ) . However, Omer et al .…”
Section: Introductionmentioning
confidence: 99%
“…There are other parameters that are used to evaluate patient radiation dose through CT examinations, including volumetric CT dose index (CTDI vol ) and dose length product (DLP). However, both of these parameters measure scanner output and neglect the patient’s body type [ 14 – 16 ]. To tackle this matter, the American Association of Physicists in Medicine (AAPM) formed a task group to devise an appropriate tool for investigating the radiation dose received by a patient during CT examination.…”
Section: Introductionmentioning
confidence: 99%
“…2 The speed of acquisition of CT scanners is an advantage that makes it so widely used in clinical examinations. The first CT scanner took approximately 300 s to acquire an image of a single slice, 3 but now hundreds of slices can be obtained just in one rotation of the X-ray tube in less than a second.…”
Section: Introductionmentioning
confidence: 99%
“…Head CT examinations in clinical practices often lead to the eye lens being exposed to the primary radiation. 3,6 The dose threshold determined by the International Commission on Radiological Protection (ICRP) for the eye lens is 500 mGy, and eye dose limit for cataract formation is 2000 mGy. 6,7 Generally, the dose for head CT examination is approximately 50 mGy.…”
Section: Introductionmentioning
confidence: 99%